Providing care for a person with late-stage dementia at home: What are carers' experiences?. (February 2020) - Dempsey, Laura; Dowling, Maura; Larkin, Philip; Murphy, Kathy
Background: It is widely reported that carers who provide care for a family member with dementia endure physical and psychological burdens. Not only do they fulfil an important role for the person with dementia but also for the wider society. This study aims to explore the experiences of carers who provide end-of-life care for a person with late-stage dementia at home. Method: Semi-structured interviews were conducted with 17 current carers and 6 past carers of a family member with late-stage dementia. Data was analysed using interpretative phenomenological analysis. Results: Four super-ordinate themes were identified which described the challenges faced by carers at different stages of their care giving journey: (1) The experience of dementia grief; (2) Parenting the parent; (3) Seeking support; (4) Death, dying and life after death. Conclusion: Dementia grief was experienced by carers as a result of a relationship change and an inability to recognise the person with dementia as their mother, father or spouse. A role transition ensued resulting in the carer adopting the role of parent. Carers expressed a desire to provide care for the person with dementia at home until the time of death; however, support is required in this area at both individual and community level. Family carers require education to help identify the dying phase which will assist to minimise the shock of death. Strong evidence suggests that the burden of care may leave family carers poorly equipped to adapt to life after the death of the person with dementia. Greater pre-death support is required to facilitate a better post bereavement adjustment.